Disease Severity and Prognosis of SARS-CoV-2 Infection in Hospitalized Patients Is Not Associated With Viral Load in Nasopharyngeal Swab - Cocconcelli, Elisabetta; Castelli, Gioele; Onelia, Francesco; Lavezzo, Enrico; Giraudo, Chiara; Bernardinello, Nicol; Fichera, Giulia; Leoni, Davide; Trevenzoli, Marco; Saetta, Marina; Cattelan, Annamaria; Crisanti, Andrea; et al. (Frontiers in Medicine, 2021)
Background. The impact of viral burden on severity and prognosis of patients hospitalized for Coronavirus Disease 2019 (COVID-19) is still a matter of debate due to controversial results. Herein, we sought to assess viral load in the nasopharyngeal swab and its association with severity score indexes and prognostic parameters. Methods. We included 127 symptomatic patients and 21 asymptomatic subjects with a diagnosis of SARS-CoV-2 infection obtained by reverse transcription polymerase chain reaction and presence of cycle threshold. According to the level of care needed during hospitalization, the population was categorized as high-intensity (HIMC, n=76) or low intensity medical care setting (LIMC, n=51). Results. Viral load did not differ among asymptomatic, LIMC, and HIMC SARS-CoV-2 positive patients [4.4 (2.9–5.3) vs 4.8 (3.6–6.1) vs 4.6 (3.9–5.7) log10copies/ml respectively; p=0.31]. Similar results were observed when asymptomatic individuals were compared to hospitalized patients [4.4 (2.9-5.3) vs 4.68 (3.8-5.9) log10copies/ml; p=0.13]. When the study population was divided in High (HVL, n=64) and Low Viral Load (LVL, n=63) group no differences were observed in disease severity at diagnosis. Furthermore, LVL and HVL groups did not differ with regard to duration of hospital stay, number of bacterial co-infections, need for high-intensity medical care and number of deaths. The viral load was not an independent risk factor for HIMC in an adjusted multivariate regression model (OR: 1.59; 95%CI: 0.46–5.55, p=0.46). Conclusions. Viral load at diagnosis is similar in asymptomatic and hospitalized patients and is not associated with either worse outcomes during hospitalization. SARS CoV-2 viral load might not be the right tool to assist clinicians in risk-stratifying hospitalized patients.